Posouzení bezpečnosti prostorového rámu při statickém zatížení - Málek, Michal (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2008)
Bakalářská práce pojednává o posouzení bezpečnosti prostorového rámu při statickém zatížení. Toto posouzení se demonstrovalo na konkrétním příkladu. Při řešení jsme využili vlastností symetrie rámu. Neznámé parametry se určovaly z deformačních podmínek v prusečíku roviny symetrie a střednice rámu, kde posuv a dvě natočení jsou nulová a dále pomocí Maxwell – Mohrovy varianty Castiglianovy věty pro určení deformace rámu. Při výpočtu napětí se vycházelo z teorie kombinovaného namáhání prutu, konkrétně z kombinace ohybu a krutu. U posuzování bezpečnosti rámu se bral ohled na nebezpečná místa vlivem zlomu a vetknutí, kde dochází ke koncentraci napětí. Výsledky analytického řešení byly ověřeny numerickým výpočtem v programu ANSYS 10.0.

This bachelor thesis deals with evaluation of safety factor of a space frame when being statically loaded. This examination was demonstrated on a particular example. In order to solve the above mentioned, we exploit the frame symmetry. Unknown parameters were identified from deformation conditions in the point of intersection of the symmetry plane and the frame centreline, where the shift and two turning angles equal zero, and further by means of Maxwell- Mohr variant of Castigliano's theorem for determination of the frame deformation. The basis for calculations of stresses was represented by the theory of combined bar loading, particularly combination of bending and torsion. When examining the frame safety we took into consideration mainly dangerous points possibly occuring through cranks and fixed supports, where stress concentration occurs. The results of analytical solution were verified by numerical calculation in program ANSYS 10.0.
Safety factor evaluation for an out-of-plane frame under static loading
Keywords: Prostorový rám; statické zatížení; bezpečnost; napětí; deformace; Castiglianova věta; kombinované namáhání; Out-of-plane frame; static loading; safety; stress; strain; Castigliano's theorem; combined loading